YC-1 induces lipid droplet formation in RAW 264.7 macrophages. Issue 1 (December 2016) - Tsui, Leo; Chang, Shwu-Fen; Huang, Hsiang-Po; Fong, Tsorng-Harn; Wang, I-Jong
Abstract Background 3-(5'-Hydroxymethyl-2'-furyl)-1-benzylindazole (YC-1) is a potential anticancer drug that may activate soluble guanylyl cyclase (sGC) and increase the level of cyclic guanosine monophosphate (cGMP). The aim of this study was to explore the effects of YC-1 on lipid droplet accumulation and foam cell formation in macrophages. Results Human-oxidized low density lipoprotein (ox-LDL) was used to induce accumulation of lipid droplets in a murine macrophage cell line, RAW 264.7. Oil red O staining showed that treatment with 20 μM YC-1 for 24 h increased the area of intracellular lipid droplets in macrophages. The results of high content screening (HCS) with the AdipoRed™ assay further revealed that YC-1 enhanced ox-LDL-induced foam cell formation. This was evidenced by an increase in the total area of lipid droplets and the mean fluorescence intensity per cell. Inhibition of cGMP-dependent protein kinase (PKG) using KT5823 significantly reduced YC-1-enhanced lipid droplet formation in ox-LDL-induced macrophage foam cells. Conclusion YC-1 induces lipid droplet formation in macrophages, possibly through the sGC/cGMP/PKG signaling pathway. This chemical should be tested with caution in future clinical trials.